Ergonomi dalam Perancangan Shelter Darurat Bencana Erupsi Gunung Semeru - Ramadhani, Ledy Fitra; Dinapradipta, Asri; Ekasiwi, Sri Nastiti N. (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 10 No 2 (2023): October 2023DO - 10.24843/JRS.2023.v10.i02.p05, 2023)
Being located on a significant ring of fire, Indonesia inevitably experiences frequent volcanic eruptions in varying degrees. Disaster mitigation for volcanic eruptions continues to be developed to minimise risks, including providing emergency shelter to those affected by the events. A series of catastrophes associated with volcanic eruptions that occur over a long period of time often requires emergency shelters till it is safe to go back home or an alternative for a new living arrangement is available and ready. Therefore, it is necessary to pay attention to the design of emergency shelters to provide both physical and mental comfort to the refugees. In this case, ergonomic aspects become pivotal and deserve serious attention. This study aims to explore the concept of ergonomics in designing emergency shelters for those who are affected by volcanic eruptions. It uses descriptive qualitative methods with a case study of impacts inflicted by Mount Semeru eruptions of East Java. It found its analysis by a thorough literature review and prior studies. Study results include references for emergency shelters that are ergonomically designed and efficiently meet needs for comfort, health, and dignity. Keywords: ergonomics; disaster emergency shelter; volcanic eruption Abstrak Sebagai negara yang terletak di Ring of Fire, Indonesia sering mengalami erupsi gunung berapi dalam beragam tingkat. Mitigasi bencana untuk erupsi gunung berapi terus dikembangkan untuk meminimalisir resiko bencana, termasuk juga dalam hal penyediaan shelter darurat bagi pengungsi korban bencana. Rangkaian bencana akibat erupsi gunung berapi yang dapat terjadi dalam jangka waktu panjang kerap menyebabkan masyarakat harus tinggal di shelter darurat selama periode bencana hingga pemulihan. Karenanya, rancangan shelter darurat perlu diperhatikan untuk dapat menyediakan kenyamanan bagi pengungsi serta kesehatan baik fisik dan mental selama periode tersebut, salah satunya dengan memperhatikan aspek ergonomi. Penelitian ini bertujuan mengeksplorasi konsep ergonomi pada shelter darurat bencana erupsi gunung berapi menggunakan metode kualitatif deskriptif menggunakan studi kasus dari Gunung Semeru di Jawa Timur. Hasil penelitian ini merumuskan aspek ergonomis dalam perancangan shelter darurat bencana erupsi gunung berapi melalui kajian literatur dan studi preseden yang pada akhirnya dapat digunakan sebagai panduan untuk merancang shelter darurat bencana yang ergonomis sehingga efektif dan efisien dalam memenuhi kebutuhan tempat tinggal darurat yang nyaman, sehat, dan bermartabat. Kata kunci: ergonomi; shelter darurat bencana; erupsi gunung berapi